2013
DOI: 10.3390/nu5020340
|View full text |Cite
|
Sign up to set email alerts
|

Selenistasis: Epistatic Effects of Selenium on Cardiovascular Phenotype

Abstract: Although selenium metabolism is intricately linked to cardiovascular biology and function, and deficiency of selenium is associated with cardiac pathology, utilization of selenium in the prevention and treatment of cardiovascular disease remains an elusive goal. From a reductionist standpoint, the major function of selenium in vivo is antioxidant defense via its incorporation as selenocysteine into enzyme families such as glutathione peroxidases and thioredoxin reductases. In addition, selenium compounds are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 90 publications
2
35
0
1
Order By: Relevance
“…The mechanism underlying the adverse effects on glucose metabolism could be that excess selenium, as well as insufficient selenium, damage the redox-methylation balance through the methionine-homocysteine cycle and so lead to excessive expression of GPx1 [36,37]. The results from animal studies have demonstrated that overexpression of GPx1 is associated with insulin resistance, hyperglycemia and obesity [38,39].…”
Section: Tablementioning
confidence: 94%
“…The mechanism underlying the adverse effects on glucose metabolism could be that excess selenium, as well as insufficient selenium, damage the redox-methylation balance through the methionine-homocysteine cycle and so lead to excessive expression of GPx1 [36,37]. The results from animal studies have demonstrated that overexpression of GPx1 is associated with insulin resistance, hyperglycemia and obesity [38,39].…”
Section: Tablementioning
confidence: 94%
“…Importantly, IBDs have been associated with an increased risk of colon cancer [1,7]. However, despite evidence on the importance of Se and selenoproteins for the cardiovascular (CV) system due to their antioxidant functions [8,9,10] and the role of Se-enriched diets in reducing colon cancer risk development [11], few data are available on the influence of Se in IBDs. Se supplementation has been reported to protect against tissue damage in chemically-induced UC by modifying the expression of genes involved in the mitochondrial regulation of cell death [12].…”
Section: Introductionmentioning
confidence: 99%
“…The polypill, which currently addresses a number of cardiovascular risk factors including hypertension, is however reductionistic, as are public health concepts of universal dietary supplementation or restrictions [76,77]. Although effective to a degree, these measures cannot address the wide population variability in response to diet, exercise and medication [46].…”
Section: Foods and Ingredients Listed By Therapeutic Class Nutrients mentioning
confidence: 99%